Вы находитесь на странице: 1из 62

..

I
1. . .
.
. .
X Y
x X f
y Y . ,
y x y = f ( x ). x
( ), y
, X - ()
, Y () .

xOy,
y = f (x ),
.

. :
y = y( x ), y = F (x ), y = g ( x ).
U

, ,
,
()
.
: ,
.
U

y=const, x
x

- ),

y = a (0 < a 1),
log a x(0 < a 1), sin x, cos x, tgx, ctgx

arcsin x, arccos x, arctgx, arcctgx.


,

, (),
.
U

:
f (x ) = x 1 x 3 , f (x ) = log 2 sin x e x , f (x ) = arctg 3 x .
,
:
1.
P ( x ) = a 0 x n + a1 x n 1 + a 2 x n 2 + K + a n 1 x + a n ,
n 0 - , a 0 = 0, a1 , a 2 , K , a n -
(), ,
n .
(
).
2.
a x n + a1 x n1 + K + a n1 x + a n
R(x ) = 0 m
b0 x + b1 x m1 + K + bm1 x + bm
.

3. ,

,
.

4. ,
, .
U

5. ( ).
u, u
x, x.
y = F (u ) u = (x ) . x
U

y = F [ (x )] - .
.

1 , 2 , , x n , ,
> 0 N = N(), x n a < n
> N.
lim x n = a .
U

, x a .

y = f ( x )
.
1. y = f ( x ) b
U

( y b ) ( x a ),
U

>0

> 0, ,
x a < f ( x ) b < . b
y = f ( x ) x a ,
lim f ( x ) = b .

x a

1. f ( x ) b1 x a ,
, lim f ( x ) = b1 , b 1
B

x a 0

.
, lim f ( x ) = b2 b 2
U

xa +0

. x 0 + 0 x 0 0 ,
x +0 x 0 .
2. f (x ) b
x , > 0
N > 0, ,
x > N f ( x ) b < .
U

2. .
.

,
, x a x .
x a , x ,
.
1. ,

:
lim (u1 + u 2 + ... + u k ) = lim u1 + lim u 2 + ... + lim u k
xa

xa

xa

xa

2. ,

.
lim u1 u 2 ... u k = lim u1 lim u 2 ... lim u k
.
:
lim u1 = a1 , lim cu1 = lim c lim u1 = c lim u1 . .
3.
, 0:

u lim u
=

lim v 0 .
v lim v
4.
u = u( x ); z = z ( x ); v = v ( x )

u z v , u v x a x
b, z = z(x) x a ( x )
.
5. x a ( x ) y
y 0 y b , b
b 0 .
6.
u = u(x ) v=v(x), x a
lim

( x ) u( x ) v ( x ) ,

lim u( x ) lim v ( x ) .
xa

x a

7. v , ..
, ,
, .. v < M,
lim v = a , < M.

-0, - .
0

, , {0 }, { }, 1
0
.

{ }


)
U

lim

x 0

sin x
x 0 (
x
U

sin x
= 1.
x

e.

1. 1 +
n

= lim 1 + .
n
n
.
: =2, 7182818284...

n :
U

.
1 +
x

, :
x

lim 1 + = .
x
x

3.
, .
.

. .
.

, y = f (x )
.
1. f (x ) x , ..
,
>0, > 0,
, x a < ,
U

f (x) > M .

f (x ) x a , lim f ( x ) = .
xa

f (x )
, , f (x ) + ,
, - f (x ) .
2. f (x )
,
M > 0 , ,
, f ( x ) M .
, f (x )
.
U

3. f (x )
x a , ,
.
U

4. f (x )
x , N > 0 ,
,
U

| x |> N , f (x ) .
1. lim f ( x ) = b b ,
x a

f (x ) x a .
3. f (x )
, lim f ( x ) = lim f ( x ) = , .. f (x )
x a

, .

1. (x )
x a x , lim ( x ) = 0 , lim ( x ) = 0 .
U

x a

1. = ( x ) 0 x a ( x )
0, y = 1 .

2.
.
3. (x )

z = z (x ) x a ( x ),
.
C 1. lim = 0 , lim = 0 , lim = 0 .
2. lim = 0 , c = const , lim c = 0 .
( x)
5.

z( x)
(x ) , 0,
.
U

,
, ,

.

1. /
, .. lim / = const 0, A = const ,
xa

, lim / = 1 / A 0 ,
xa

.
2. /
, .. lim / = 0 (
lim / = ),

, ,
,
.
3.
k- ,
k , ..
k
lim / = A 0.
U

x a

4. /
, .. lim / = 1 ,
x a

( ~ ).
U

= f(x)
0 0 .
0 = f(x 0 ).
= 0 +,
. ,
:
0 + = f(x 0 +).
= f(x 0 +)
f(x 0 ).
B

. = f(x)
= 0 ( 0 ),
0
lim y = 0
U

UBU

UBU

UBU

UBU

x 0

, ,
lim [ f ( x 0 + x ) f ( x 0 )] = 0 .
x 0


lim f ( x 0 + x ) = f ( x 0 ) .
x 0

. = f () 0
U

UBU

:
1) 0,
2) lim f ( x ) , lim f ( x ) ,
B

x x0 + 0

x x0 0

3)
lim f ( x ) = lim f ( x ) = f ( 0 ).
x x0 + 0

x x0 0


, 0 = f () . = 0
.
. = f () ,

lim f ( x ) = f ( x 0 + 0) lim f ( x ) = f ( x 0 0) ,
B

x x0 + 0

x x0 0

1) lim f ( x ) lim f ( x ) , = 0
x x0 + 0

x x0 0

1- ,
2) lim f ( x) = lim

x x0 +0

x x0 0

f ( x) ,

= 0 , = 0 .

, .
B

1. = f ()
[a,b], [a,b]
= 1 ,
f ( 1 ) f (),
, = 2 ,

B

f ( 2 ) f (). f ( 1 )
= f () [a,b], f
( 2 ) = f ()
[a,b].
2. = f ()
[a,b],
, a b
=, .
3. = f ()
[a,b].
f ()= , f (b) =B, ,
, =,
b , f ()= .
B

4. . ,
.
.

.
.
.
y ,
, x , x 0, ..

f ( x0 + x) f ( x0 )
y
= lim
x 0 x
x 0
x
lim

f(x) x.
dy
.
f ( x), y ,
dx
.
,
=f (x) ,
. .
U

y=f(x) x 0 , ..
B

f ( x 0 + x )
y
= lim
,
x 0 x
x 0
x

lim

f(x)

x 0 .
[a ,b], [a,
b].
. f(x)
x 0 , .
, , , ,
, ..
.
U

UBU

UBU

1. 0, ..
, = const , y = 0 .
2.
, ..
y=c

, = const , y = cf (x ) .
3.

, ..
y = u( x ) + v ( x ) , y = u ( x ) + v ( x ) .
y = cf (x )

4.



, ..
y = u v, y = u v + v u .
5.
,
,
,
..
y=

u
v

, y = u v v u .
2
v

=f(x), .. ,
: y=F(u), u =(x) y=F((x)).
y=F(u) u
.
. u=(x) x
u x = ( x ) , F(u) u
y u = F (u ) , y=F((x))
x ,
y x = Fu (u ) x ( x ) , u
u=(x).

1. y = const ,
n

2. y = x ,

y' = 0 .
y ' = nx n 1 .

3. y = x ,

y' = 1 .

4. y = x ,

y' =

1
,
x
6. y = sin x ,
7. y = cos x ,
5. y =

8. y = tgx ,
9. y = ctgx ,
10. y = arcsin x ,
11. y = arccos y ,
12. y = arctgx ,
13. y = arcctgx ,
14. y = a x ,
15. y = e x ,
16. y = log a x ,
17. y = ln x ,

.
2 x
1
y' = 2 .
x
y ' = cos x .
y ' = sin x .
1
.
y' =
cos 2 x
1
.
y' =
sin 2 x
1
.
y' =
1 x2
1
.
y' =
1 x2
1
.
y' =
1+ x2
1
.
y' =
1 + x2
y ' = a x ln a .
y' = e x .
1
y ' = log a e .
x
1
y' = .
x

1. y = Cu(x ) ,
2. y = u( x ) + v ( x ) ,
3. y = u( x )v ( x ) ,

y ' = Cu ( x ) .
y = u ( x ) + v ( x ) .
y = u ( x )v ( x ) + u( x )v ( x ) .

4. y =

u( x )
,
v( x)

y' =

u ( x)v( x) u ( x)v ( x)

v 2 ( x)
5. y = f (u ), u = ( x ). y = f u (u ) x ( x ) .
1
y = f ( x)
f ' x ( x) =
6.
,
.
x' y
x = ( y)

y (x)
y = (t ), x = (t ) , t 0 t < T .

,
x = (t ) t = (x ) , y = [(x )]
:
'
y'
1
y' x = t = t .
,
y ' x = ' t ' ( x ) ,
' x =
' t x' t
't


5.

.
.
.
.

y=f(x)

[a,b].
y
.
, y = f ( x ) = lim
x 0 x
, , ,

y
= y + ,
x
, .. 0 0.
y = y x + x .
y ,
,

x .

y x
dy.
dy= y x .

. .
dy = f ( x )dx .
dy
, f ( x ) = ,
dx
U

y=f(x) [a,b].
y x.
,
. y f (x ) .
U


y . y IV , y V , y VI .
n- f(x)
(n-1)-
y ( n ) . y ( n ) = ( y ( n 1) ) -
.

6. , , .
.
7. .
.

8.
.
. , ,
. .
.

,
.

.
1. 1) f(x),
[a,b], ,
[a,b] , .. f ( x ) 0 .
2) f(x) [a,b]
(a,b), f ( x ) > 0 x (a,b),
[a,b].

() , :
2. 1) f(x),
[a,b], ,
[a,b] f ( x ) 0 .
2) f(x) [a,b]
(a,b), f ( x ) < 0 x (a,b),
[a,b].

1. f(x) x=a ,
f(a+x)<f(a) x.
2. f(x) x=a ,
f(a+x)>f(a) x.
.

1
(

). f(x)
x=x 1 ,
, .. f (x 1 )=0.


,
x.
B


, ,
.
.
, : f () =0
f () .
B

, f () =0 f ()
, .
2. ( ).
f(x) ,
x 1
( , x 1 ).
+
, x=x 1 .

+, x=x 1 .
B

, .
1. ,
(a,b),
.

2. ,
(a,b),
.
1. (a,b)
f`(x) , .. f ( x ) <0,
.
2. (a,b)
f ( x ) >0, .
. ,
, .

,
.
3. y=f(x).
f (a)=0 f (a) x=a
, x=a
.

. L ,
M ,
M L 0 .

.
1. . ,
lim f ( x ) = lim f ( x ) = , x=a
x a +0

x a 0

, ,
.
x=a , x a
f(x) , x=a .
2. .
y=f(x) ,
: =kx+b.
k b: k = lim

f ( x)
; b = lim [ f ( x ) kx ].
x
x

, .

,
:
1) ;
2) ;
3) (, ,
);
4) (, );
5) ( f (x)=0 f (x)` );
6) ( f (x)=0
f (x) );
7) ;
8) ;
9) , .

.

9. .

. .
.
: F(x)
() (a, b), F(x)
(a, b) F (x ) = f (x ) dF(x)=(x)dx
x (a, b) .
() F(x),
.
1. F(x) ()
(a, b), F() + C , C -
.
2. F(x) ()
() (a, b),
: () F(x) = C x (a, b) .
. F(x)
(), F (x ) + c
()

f ( x)dx .
F(x) (),
:

f (x )dx = F (x ) + c .

() ().
, , .
1.

f (x )dx = f (x ) .

2.
:
d

f (x )dx = f (x )dx .

3.
:

dF(x) = F(x) + .


x a +1
1. x a dx =
+ c (a 1) .
a +1
dx
2.
= ln x + c (x 0) .
x
ax
3. a x dx =
+ c (a > 0; a 1) .
ln a

4. e dx = e + c .
5. sin xdx = cos x + c .
6. cos xdx = sin x + c .
dx
7.
= tgx + c .
cos x
x

dx

8.

sin

9.

10.

x
dx

1 x
dx

1+ x

11.

12.

13.

= ctgx + c .

= arcsin x + c .
arccos x + c

= arctgx + c .
arcctgx + c

dx
2

x a
dx
2

= ln x + x 2 a 2 + c .

1
a+x
ln
+c.
2a a x

arcsin + c

dx

a
=
2
2
a x
arccos x + c

x
1
arctg + c

dx
a
a
=
14. 2
2
a +x
1 arcctg x + c
a
a

1.
:

Af (x )dx = A f (x )dx .

2.

:

[ f (x ) + g (x )]dx = f (x )dx + g (x )dx

( ).
3.

f (x )dx = F (x ) + c ,
1

f (ax + b)dx = a F (ax + b) + c .



, ()
, (t) (t)
t.

f (x )dx = f [ (t )] (t )dt .
x = (t) ,
,
.


u = u(x) v = v(x)
.

udv = uv vdu .
.

udv

vdu, .

10.
.
. .
- :

Pn (x )
Qm ( x )
(m>n) :
R( x ) =

)(

Qm ( x ) = a m (x x1 )k (x x2 )l ... x 2 + p1 x + q1 x 2 + p 2 x + q 2 ...

:

Pn (x )
Ak
A1
A2
=
+
+ ... +
+
2
Qm (x ) x x1 ( x x1 )
(x x1 )k
Bl
B1
B2
+
+
+ ... +
+
2
( x x2 ) ( x x2 )
(x x2 )l
+
+

M 1 x + N1
x 2 + p1 x + q1
P1 x + Q1
2

x + p2 x + q2

M 2x + N2

(x

(x

+ p1 x + q1
P2 x + Q2

+ ... +

+ p2 x + q2

(x

+ ... +

M S + NS
2

(x

+ p1 x + q1
PP + QP
2

+ p2 x + q2

+ ...

A1 , A2 ,... Ak ; B1 , B2 ,...Be ,...M 1 , N1 , M 2 , N 2


.. .
,
, .

11. .

1.

, sinx cosx:

R(cos x, sin x )dx .




t. :

tg

x
=t .
2

sinx, cosx dx t dt;


2dt
.
x = 2arctgt ; dx =
1+ t2
2dt
2t
1 t2
sinx =
;
cos
; dx =
.
x
=
2
2
1+ t
1+ t
1+ t2
,
.
2.
.

1) R (sin x ) cos xdx ,

sinx = t, cos xdx=dt

R(t )dt.

2) R (cos x )sin xdx ,

cosx = t, sin x dx= dt


.

3) tgx,
dt
tgx = t , x = arctgt , dx =

1+ t2
.

4) R (sin x, cos x ) dx , sinx cos x


,
tgx = t.

5) sin m x cos n xdx .


.
)

sin

x cos n xdx , m n ,

. , n
. n=2+1 :

sin x cos xdx = sin x cos


= sin x(1 sin x) cos xdx.
2 p +1

2p

x cos xdx =

sinx = t, cos xdx=dt.


,

sin m x cos n xdx = t m 1 t 2

) dt,
p

t.
)

sin

x cos n xdx , m n .

m =2p, n =2q.
:
1
1
sin 2 x = (1 cos 2 x), cos 2 x = (1 + cos 2 x).
2
2
,

sin

2p

x cos2q xdx =

2 p q (1 cos2x)
+

(1 + cos 2x) dx.

, ,
cos 2x .
, ).
.


,
.
1. R(x, n x, m x , )
k 1/m, 1/n, ...

x= t k , dx = kt k 1dt.

t
t.
2.

ax + b n ax + b
R x; m
;
;... .

cx + d cx + d

,

. :
ax + b
= tN,
cx + d
N m, n,

12. . .
. .
.
: , ,
.

, .
y = f(x) [a,b],
f(x) >0. , , y =
f(x), : x = a x = b.
,
[a,b] .
.
,
S n , [a, b]
( ):
B

n1

S=

lim

max xk 0

f (

k ) x k

(1)

k =0

max x k - .
f(x)
[a, b ]
k .
.
(1) max x k 0
,
k ,
f(x) [a, b ] :
b

f ( x)dx .
a

, b
. , :
b

n1

f ( x)dx =

lim

max xk 0

f (

k ) x k

k =0

,
f(x) a b.


.
,
b

dx = b a .
a

f ( x)dx = f ( x)dx , a=b, f ( x)dx = 0 .


,
[a, b ] , .

1.
:
b

Af ( x)dx = A f ( x)dx .
2. f(x) g(x) [a, b ] ,

:
b

[ f ( x) + g ( x)]dx = f ( x)dx + g ( x)dx .


3. [a, b ] ,
(
a, b, ).

f ( x)dx = f ( x)dx + f ( x)dx .


4. f ( x) 0

[a, b]

(a<b),

f ( x)dx 0 .
a

5. f(x) g(x) [a, b ] (a<b)


f ( x) g ( x) ,
b

f ( x)dx g ( x)dx ( , a<b).


a

6. f(x) [a, b ] (a<b)


m , [a, b ]
m f ( x) M ,
b

m(b a)

f ( x)dx M (b a) .
a

7. f(x) [a, b ] ,
(c (a, b )) ,
:
b

f ( x)dx = f (c)(b a) .
a

[a, x ] , a x b .
[a, b ] , [a, x ] ,
:
x

f ( x)dx = f (t )dt .


:
x

( x) =

f (t )dt

(a x b ) .

. f(x) [a, b ] ,
(x) [a, b ] ,
( x ) = f ( x ) .

-.

. f(x) [a, b ]
F(x) - f(x) [a, b ] ,
:
b

f ( x)dx = F (b) F (a) .


a

-.
b

F (b) F ( a ) = F ( x) a - .


u(x) v(x)

[a, b] .

udv = uv a vdu .
a

, ,
.

f ( x)dx ,

f(x)

.

x = (t ) .
:
. :
1. f(x) [a, b ] .
2. (t ) (t ) [ , ]
a (t ) b t ( ) = a; ( ) = b .
3. f [ (t )] [ , ]

a f ( x)dx = f [ (t ) (t )dt ] .

1. f ( x) 0 [a, b ] ,

b

S=

f ( x)dx .
a

2.
b

s=

1 + [ f ( x )]2 dx .

3. y = f(x) Ox
b

Vx =

[ f ( x)] dx .
2

13.
. .
b

f ( x)dx , :
a

1. [a, b ] .
2. f(x) [a, b ]
( ).
,
.

( )
1. f(x)
a x < +
N + :

f ( x)dx = lim

N +

f ( x)dx .
a

,
. ,
.
.
( )
.
f(x) ( , a ) , :
a

f ( x)dx = lim

f ( x)dx .

f(x) ,

f ( x)dx = f ( x)dx + f ( x)dx .

, , ,
,
.
,
.
.
1. x [a,+ ) :
0 f ( x) g ( x) ,

:
+

1.

g ( x)dx ,

a
+

2.

f ( x)dx .
a

f ( x)dx , g ( x)dx .
a


( )
f(x) [a, b ]
( ),
[a, b] d ,
f(x) .
a b
.
b

f ( x)dx =

f ( x)dx +

f ( x)dx +

f ( x)dx .
d

0 ,
:

lim

f ( x)dx = f ( x)dx .

,
.

. f(x) a < x b , =
,
b

f ( x)dx = lim f ( x)dx. .


a

a+

2. a x < b ,
0 f ( x) g ( x) , f(x) g(x) a x < b ,
x=b . :

1.

2.

a
b

g ( x)dx , f ( x)dx ;
b

f ( x)dx , g ( x)dx .
a

II

14. .
,

, .
.
(, ), ,

z, z
:
z = f (x, y).
2
2
: z =ln ( x + y 2) .
z.
D z. (,
) (, ).
. - M 0 ( 0 , 0 )
M 0. M0
( 0 , 0 )

( x x 0 ) + ( y y 0 ) < ..
1 D,
,
.
2 D,

D, .
D
.
B

D ( D ),
. D ,
.
z = f (, )
, ..

z = f (,)
D.


, .
n=2.
.
f (, ) 0 , y 0 ( 0 ),
B

>0 > 0 , -
B

0 ( 0 , 0 )
B

f ( x, y ) A < ,

:
lim f ( x, y ) = A .
x x0
y y0

lim f ( x ) = A ,
x x0

lim

x x0 + 0

f ( x) = A ,

lim

x x0 0

f ( x) = A .

f (, )
,

.
f(,) ,
lim f ( M ) = 0 .
M M 0

f (,) 0 ( 0 , 0 ),
0
B

lim f ( x, y ) = f ( x 0 , y 0 )

x x0
y y0

f (, ) ,
.
1 ( 1 , 1 ) f (, ),
,
1
.
B



z =f (, )
0 ( 0 , 0 ) . = 0 ,
. z =f (,
0 ). 1 ( +, 0 ).
B

z = f ( 1 ) - f ( 0 )= f ( +, 0 ) - f ( 0 , 0 ).
B

z
z.
B

xz

x
0 , z
0 ( 0 , 0 ).
.

z x , f x ( x 0 , y 0 ) ,

z f ( x0 , y 0 )
,
. ,
x
x

z
z
= lim x =
x x 0 x
f ( x0 + x, y 0 ) f ( x0 , y 0 )
= lim
= = f x ( x0 , y 0 ) .
x 0
x

: , .

0 ( 0 , 0 ) 2 ( 0 , 0 +)
z
( = 0 , : z= f( 0 , )).
B

y z = f ( 2 ) - f ( 0 )= f ( 0 ,y 0 + ) - f ( 0 , 0 ).
B

yz

0,

, z
.
z y , f y ( x 0 , y 0 ) ,

z f ( x 0 , y 0 )
,
.
y
y


yz
f ( x 0 , y 0 + y ) f ( x 0 , y 0 )
z
= lim
= lim
= f y ( x 0 , y 0 ) .
y

0
x 0
y
y
y

z
z


x
y
z 0 ( 0 , 0 )
.

,
.
z
,

y
L
:

z
= tg .
y M 0

z

x
z =f (, )

= 0 , ..
B

z
= tg .
x M 0

15. .
. ,
. .

f (x,).
0 ( 0 , 0 )
. 0 ( 0 , 0 ) ( ,)
B

= x 0 + x, = 0 +
:
B

z = f () - f ( 0 ) = f (x 0 + x, 0 + ) - f (x 0 , 0 ),
B

.. , , ,
.
z = f (x, )
0 ( 0 , 0 ), ,
:
B

z = x + y + , 0 0
. x + y x
y f (x, )
0 ( 0 , 0 )
dz = x + y.
:
z
z
dz=
x +
y. x =d y= d.
x
y
d z = f x ( x, y ) d x + f y ( x, y ) d y (
B

(, ). , d z =

dx z +

d y z -

.
.

.


z = f (u, v),
u v , ,
:
u (x, )

v (x, )

z

, x :
z = f [u(x, ), v(x, )].

z z u z v
+
=
;
x u x v x

z z u z v
=
+
.
y u y v y

1.
:

w = f ( x, y , z ), x = x (t ); y = y (t ); z = z (t ).
, , w = f ( x , y , z ),
t: w=w(t),

dw w dx w dy w dz
=
+
+
dt x dt y dt z dt

.
2.
.

w = f (t , x , y , z ), x = x (t ); y = y (t ); z = z (t ).
f dx f dy f dz
dw f
=
1 +
+
+
x dt y dt z dt
dt t
.

.

z = f (u,v), u =u (x, ), v =v (x, )
.

z
z
dz = du + dv .
u
v
,
, u v .
,
, u v
. .


z = f (u,v).
:
z
z
= f x ( x, y )
= f y ( x, y ) .
x
y
, ,
: .
.

:
2z
z
2 z z
( x, y ) ;
xx ( x, y ) ;
= = f xy
=
f
=

2
y x
x x
xy
x

2z
yx

z
2z
z
( x, y ) ;
( x , y ) .
= f yx
=
= f yy
2
x y
y y
y

( x, y ) , f xy
( x, y ) ,
f yx

, .
.
,
2z
2z
=
.
yx
xy

dz = f x ( x, y )dx + f y ( x, y )dy .

.


d 2 z = d [dz ] .

( x, y )dxdy + f yy
( x, y )dy 2 .
( x, y )dx 2 +2 f xy
d 2 z = f xx
,
F(x,y,z)=0,
D z= f(x,y),
: F(x,y, f(x,y))=0.
, :
Fx x x + Fz z x = 0 , .. Fx + Fz z x = 0

Fx ( x, y , z )
.
Fz ( x, y , z )
:
z x =

z y =

F y ( x, y , z )

.
Fz ( x, y , z )
,
Fz ( x , y , z ) 0 .

16. , .
.
.


:
u=f(x, y, z).

u
,
y

u
,
x

.
:
l 0 ,
.
0 (x 0 ,y 0 ,z 0 )
B

r
l0 .
1 ( 0 + x, y 0 + y, z 0 + z)
B

= x 2 + y 2 + z 2
0 . 0 1 u=f(M)
u= f(M 1 ) f(M 2 ).
u f ( x 0 + x , y 0 + y , z 0 + z ) f ( x 0 , y 0 , z 0 )
,

, u = f(M) 0
l .
u
u
: ul ;
; u lr ; r .
l
l
, :
B

u( x 0 + x, y 0 + y, z 0 + z ) f ( x 0 , y 0 , z 0 )
u
= lim
l 0

l0 :

r
l 0 = {cos , cos , cos }.

u u
u
u
=
cos +
cos +
cos .
l x
y
z

u=f(x,y,z)

l 0 = {cos , cos , cos }



r r r
i , j, k .
.


u=f(x,y,z). M 0 (x 0 ,y 0 ,z 0 )

.


.
.
u=f(x,y,z) M 0 (x 0 ,y 0 ,z 0 )
. 0
:
B

f ( x0 , y0 , z0 ) f ( x0 , y0 , z0 ) f ( x0 , y0 , z0 )
;
;

.
x
y
z

0 ,
.
grad u (M 0 )
B

grad f ( x 0 , y 0 , z 0 ) .
,
u r u r u r
i+
j+
k.
x
y
z

.
,
gradu ( M ) =

( =

) , ..

.
. u=f(x,y,z)
0 (x 0 ,y 0 ,z 0 )
,
.
.
B

.

z= f(x,y), 0 (x 0 ,y 0 )
.
0 (x 0 ,y 0 ))
z = f(), 0
(0< d (M 0 M) < )
B

f () <f ( 0 ) z = f () f ( 0 ) <0.
B

0 (x 0 ,y 0 )
z=f(), 0
(0< d (M 0 M) < )
B

f () > f ( 0 )
B

z = f () f ( 0 ) > 0.

.
:
1 0.
B

. ( ). z= f(x,y)
0 (x 0 ,y 0 ) ,

f x ( x 0 , y 0 ) = 0 ; f y ( x 0 , y 0 ) = 0 .
B

,
,
.
().
, .

.

. z= f(, )

0 ( 0 , 0 ), 0
f y ( x 0 , y 0 ) = 0
(.. 0
f x ( x 0 , y 0 ) = 0 ;
B

). :
( x 0 , y 0 ) = B , f yy
( x 0 , y 0 ) = C .
( x 0 , y 0 ) = A , f xy
f xx
:
1. = AC B 2 >0, 0 ( 0 , 0 ) f(,
) , , < 0 ,
> 0.
2. = AC B 2 <0, 0 ( 0 , 0 )
.
3. = AC B 2 =0, .
B

17. .

.
.
. z
=x+iy, x y , i
: i 2 = 1.
y , ,
z :
x = Re z , y = Im z.
1)
z = x + iy.
z 1 = x 1 + iy 1 z 2 = x 2 + iy 2
(z 1 = z 2 ) ,
P

x1 = x 2, y1 = y2.
B

z = x + iy,

z = x i y.

2)
r - - z ,
O. (. 1).
r , ,
z :

r = | z |; = Arg z.

r = | r | = x2 + y2 .

tg =

y
.
x

z:
= Arg z ( < Arg z < + ) .

,
, 2.
Arg z
:
= arg z ( < ) (0 < 2 ) .
.

:
z = r (cos + i sin ) .

,
.
z1 = x1 + i y1 z 2 = x 2 + i y 2 .
)
:
z1 z 2 = ( x1 x 2 ) + i ( y1 y 2 ) ,

)
, , i 2 = -1:
z1 z 2 = ( x1 + i y1 )( x 2 + i y 2 ) =
= (x1 x 2 y1 y 2 ) + i ( x1 y 2 + x 2 y1 ).
P

) ,
:
:

z1
x + iy1 ( x1 x 2 + y1 y 2 ) + i ( y1 x 2 x1 y 2 )
= 1
=
.
z 2 x 2 + iy 2
x 22 + y 22
) .
z :
z = r (cos + i sin ) .

: z n = r n (cos n + i sin n ) .
) .
n- z
w (w= n z ), w n =z.
z w :
z = r (cos + i sin ) w = (cos + i sin ).
.
w n = z, n (cos n + i sin n ) = r (cos + i sin )
n = r , n = + 2k (k = 0 , 1,...).
P

= n r -


+ 2k
(k= 0,1,2,... ).
r, =
n
+ 2k
+ 2k

wk = n z = n r cos
+ i sin
.
n
n

, z 0 n
n, .

18.
. . .
.
.
, ,
= f(x) y , y ,..., y ( n ) .

:
F ( x, y , y , y ,..., y ( n ) ) = 0.
= f(x)

, .
.
,
.
.
= f(x), ,
, .

F ( x, y , y ) = 0.
y ,
= f(x, ). ,
.
.


= (, ),

:
)
;
) = 0 = 0 ,
= 0 , = (, 0 )
.


(, , ) = 0,
B

.
.
.
= (, 0 ), = (, ),
.
(, , 0 )=0
.

,
.
.
,
.
B



dy
= f 1 ( x ) f 2 ( y ),
(1)
dx
, ,
, .
, (, f 2 ( y ) 0) :
1
dy = f 1 ( x )dx. .
(2)
f 2 ( y)
,
,


. , ,

1
dy = f1 ( x)dx + C .
f 2 ( y)
(2)
, (1)
.

19.
.
. .

. f(x, y)
n- ,

f( x, y) = n f( x, y).
.
dy
= f ( x, y )
dx
, f (x, y)
.

= 1 / x
.


.

.
dy
+ P( x ) y = Q ( x ) ,
(3)
dx
P(x ) Q ( x ) - .

:
= u (x) v (x) .
,
(3).
.

20.
.

.
,
.
n-

F ( x, y , y , y ,..., y ( n ) ) = 0
, n- ,
y (n) = f ( x, y, y , y ,..., y (n1) ) .
.

n-
y = ( x , C1 , C 2 ,..., C n ) ,
n C1 , C 2 ,..., C n , :
)
C1 , C 2 ,..., C n ;
)
y x = x0 = y 0 ,
y x= x0 = y 0 , ... ,
y (n1) x= x0 = y 0 (n1)
C1 , C 2 ,..., C n ,
y = ( x , C1 , C 2 ,..., C n ) .
( x , C1 , C 2 ,..., C n ) = 0
.
,
C1 , C 2 ,..., C n ,
.

,

1.
d2y
dy
= f ( x, ) ,
2
dx
dx

.
dy
d 2 y dp
= p . 2 =
.

dx
dx
dx
,
dp
= f ( x, p )

dx
. ,
dy
= p
= (, 1 ),
dx
B

y =

p( x, C )dx + C
1

2.
d2y

dy
),
dx
dx
.

dy
= p,
dx
.
d 2 y dp dp dy dp
=
=
=
p.
dx dy dx dy
dx 2
,

dp
p
= f ( y, p) .
dy
,
1 :
= (, 1 ).
,
,
.
2

= f ( y,

21.

.
.
.

. n-
,
y , y ,..., y ( n ) , ..

a 0 y ( n ) + a1 y ( n 1) + ... + a n y = f ( x ) ,
(4)
a 0 , a1 ,..., a n f (x ) - ,
a 0 0 ,
. ,
a 0 , a1 ,..., a n f (x ) ,
a 0 = 1 ( 1,
). f (x ) ,
, .
f (x ) 0,
.
f (x ) 0,
y ( n ) + a1 y ( n 1) + ... + a n y = 0

.
1. 1 2

y + a1 y + a 2 y = 0 ,
1 + 2 .
2. 1
, 1
.
B

. (4) 1 2
[,b],
y
, .. 1 const .
y2

.
3. 1 2
(4),
= 1 1 + 2 2
1 2 ,
.
B




y + py + q y = 0 ,

(5)

p q .

y = e kx , k = const;
y = ke kx ; y = k 2 e kx .

(5),
k 2 + pk + q = 0.
(6)
(6)
(5).
, ; k 1
k 2 .
B

p
p2
p
p2
+
q, k 2 =
q
.
2
4
2
4
:
1. k 1 k 2
;
2. k 1 k 2 ;
3. k 1 k 2 .
k1 =

.
1.
: k 1 k 2 .
y = C1 e k1 x + C 2 e k 2 x .
B

2.
. k 1 = k 2.

y = C1 e k1 x + C 2 xe k1 x = e k1 x (C1 + xC 2 ) .
B

3. .
,
k 1 = + i ,
k 2 = i ,

p2
.
4
(5)

y = e x (C1 cos x + C 2 sin x ) ,
1 2 - .
= p / 2,

= q


(7)
y + a1 y + a 2 y = f ( x ).

:
.
-
* y

y + a1 y + a 2 y = 0.

= y + *
(7).

(8)




(9)
y + py + qy = f (x ) ,
p q - .

,
.
1. (9)
, ..
f ( x ) = Pn ( x )e x ,
Pn ( x ) - n . :
)

k 2 + pk + q = 0.

y = Q n ( x ) e x .
)
:
)
:


y = xQ n ( x )e x .

y = x 2 Q n ( x )e x .

2.
f ( x ) = P( x )e x cos x + Q ( x )e x sin x ,
P ( x ), Q ( x ) - ,
:
) + i
, (9)

y = U ( x )e x cos x + V ( x )e x sin x ,
U ( x ), V ( x ) - ,
P ( x ), Q ( x ) ;
) + i
, (9)
y = x[U ( x )e x cos x + V ( x )e x sin x ] .
,
, (9)
P ( x ), Q ( x ) , ..,
P ( x )e x cos x Q ( x )e x sin x .